OBSTETRIC AND PSYCHOLOGICAL CARE FOR PREGNANT WOMAN WITH HYPEREMESIS GRAVIDARUM WITH MODERATE ANXIETY - Hesti Yuniastutiningsih; Dini Latifatun Nafi'ati (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2021)
Physical and psychological changes experienced by pregnant women, especially hormonal changes, cause symptoms of nausea and vomiting in early pregnancy. Excessive nausea and vomiting in early pregnancy and persist throughout pregnancy will cause physical and psychological complications. The existence of psychological problems in pregnant women can predispose to nausea and vomiting which then worsens. Emotional problems are also associated with the incidence of nausea and vomiting becoming more severe. Methods: the authors conducted extensive searches by scientific journals through trusted and frequently used databases, namely PubMed, Springer, and Science Direct. The keywords used were